Status of occurrence of Livistona jenkinsiana Griff. in Bangladesh - Uddin, Mohammad Zashim; Kibria, Md Golam; Sarker, Amit; Roy, Alokash (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not available Bangladesh J. Plant Taxon. 27(2): 435-438, 2020 (December)